Electroacupuncture ameliorates depression-like behaviors in rats with post-stroke depression by inhibiting ferroptosis in the prefrontal cortex - Gao, Jing; Song, Xiaolei; Feng, Yixuan; Wu, Lihua; Ding, Zhimin; Qi, Shikui; Yu, Mingyue; Wu, Ruonan; Zheng, Xinyue; Qin, Yanyan; Tang, Yuchuang; Wang, Mengyu; et al. (Frontiers in Neuroscience, 2024)
IntroductionPost-stroke depression (PSD) is the most common complication following a stroke, significantly hindering recovery and rehabilitation in affected patients. Despite its prevalence, the pathogenesis of PSD remains poorly understood. Electroacupuncture (EA) has shown antidepressant effects, yet its neuroprotective properties are not well defined. Ferroptosis, a recently identified form of cell death, is implicated in the pathological processes of stroke and is associated with the development of depression-like behaviors. So we aimed to investigate whether PSD induces ferroptosis, identify potential therapeutic targets within these pathways, and elucidate the underlying mechanisms in this study.MethodsMale Sprague-Dawley rats were subjected to middle carotid artery occlusion and chronic unpredictable mild stress to model PSD. To explore the role of ferroptosis in the effects of EA, the ferroptosis inducer erastin was administered into the rats’ lateral ventricles, followed by 14 days of EA treatment, with sessions lasting 30 minutes per day. The Zea-Longa score was used to assess neurological deficits, while the sucrose preference test, elevated plus maze test, and open-field test were employed to evaluate depression-like behaviors in the rats. Hematoxylin-eosin, Nissl, and Perl’s staining were used to observe the morphological changes and iron deposition in the prefrontal neurons. Transmission electron microscopy provided detailed observations of mitochondrial morphological changes in neurons. We utilized activity assay kits, enzyme-linked immunosorbent assay (ELISA), and Western blotting to explore potential molecular mechanisms underlying the effects of EA.ResultsEA can reduce neurological deficits and enhance the spontaneous activity and exploration behavior of rats. In addition, EA could inhibit prefrontal cortex neuronal ferroptosis by reducing iron deposition, decreasing lipid peroxidation, and enhancing antioxidation.DiscussionEA improved depression-like behaviors, mitigated mitochondrial damage, and inhibited ferroptosis in prefrontal cortex neurons. Notably, the administration of erastin further enhanced these effects. In conclusion, EA appears to improve PSD by inhibiting ferroptosis in the prefrontal cortex.